DIVERSITY OF SPINAL TUBERCULOSIS FINDINGS ON MAGNETIC RESONANCE IMAGING: A STUDY FROM A TERTIARY CARE HOSPITAL - Maimoona Afsar,; Shahab, Aymen; Samad, Mehreen; Wahid, Ghazala; Rehman, Mahnoor; Shah, Rabia (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the spectrum of findings on Magnetic Resonance Imaging (MRI) in patients with spinal tuberculosis (TB) in a tertiary care hospital. Methodology: From January 2019 to December 2020, this retrospective study was carried out at the Hayatabad Medical Complex (HMC), Peshawar, Department of Diagnostic Radiology. In total, 120 TB patients were sampled for this research. A total of 45 samples were found to be TB cases and were further investigated in this study. Results: Out of those 45 patients 19 (42.2%) were female and 26 (57%) were male. In 45 patients only 9 (20%) gave a history of previous tuberculosis. Spondylitis at a single level was observed in 3 (6.7%) patients, 37 (82.2%) patients had spondylitis at multiple levels, and 5 (11.1%) did not develop any spondylitis. Conclusion: This study concluded that magnetic resonance imaging is costly but valuable for the investigation of spinal TB. It is a variety of presentations that can cause a diagnostic dilemma so by looking into the most repetitive and common findings we can achieve diagnostic accuracy for spinal TB.